A study of acoustic emission in tensile test for metallic materials - Mohd Zambri, Abidin (2010)
This project is described about the research and experimental study of Acoustic Emission (AE) properties for metallic material during tensile test. This project involves small analysis of the metallic materials which consists of aluminum, copper, zinc, mild steel and galvanized iron. Acoustic emission is defined as the transient elastic energy that is spontaneously released when materials undergo deformation, fracture, or both. It forms the basis of one of the few Nondestructive Testing (NDT) methods that provides means of evaluating structural integrity by the detection of active flaws that may ultimately cause failure of the material or structure. Tensile test is a common and important test that provides a variety of information about the material being tested, including the elongation, yield point, tensile strength, and ultimate strength of the material. Detection of (AE) represents actual detection of fracture events as they occurred when material undergo to crack. The specimens used for tensile test are followed the American Society for Testing and Material Standard (ASTM) which is ASTM E8. The Acoustic Emission (AE) total counts obtained in different specimens for specific strain levels have been analyzed by regression analysis approach of data analysis. The results indicate that AE sources are more frequent between yield and ultimate tensile strength. This happen at the crack location where it will emits higher event of acoustic emission. All the material have a different types of properties, it was show the different stress strain curve after the experiment. From the stress-strain curve, the softer material is more plastic behavior compared than hardness materials. Galvanized iron are more strength others than material. It was prove that the galvanized iron reaches the maximum ultimate tensile strength followed by mild steel, zinc, copper and aluminum. Aluminum obtained less of acoustic emission activity. The time taken to finished the deformation of tensile testing also less than others material. However the (AE) activities for each of material are too slow because the small thickness of the specimen has affected the (AE) signal during tensile loading. It was proved that, Acoustic emission is a very versatile, non-invasive way to gather information about a material or structure.